Egyptian goose (Alopochen aegyptiacus) : sensory, biochemical and physical meat quality as affected by gender, diet and ageing - Geldenhuys, Greta (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD(Food Sc))--Stellenbosch University, 2014.